Long-term Results of a Combined Procedure of Cataract Surgery and Descemet Membrane Endothelial Keratoplasty With Stromal Rim. Issue 5 (May 2021) - Studeny, Pavel; Hlozankova, Katerina; Krizova, Deli; Netukova, Magdalena; Veith, Miroslav; Mojzis, Peter; Piñero, David P.
Abstract : Purpose: To evaluate the long-term results of combining cataract surgery, intraocular lens (IOL) implantation, and Descemet membrane endothelial keratoplasty with peripheral stromal support (DMEK-S). Methods: The outcomes of 107 eyes of 37 patients who had undergone a combination of cataract surgery, IOL implantation, and DMEK-S between October 2007 and February 2015 were retrospectively evaluated. The average follow-up duration was 18.2 ± 18.3 months (range, 6–84 months). Changes in uncorrected and corrected distance visual acuity, spherical equivalent, and corneal endothelial cell density were analyzed. Intraoperative and postoperative complications were also recorded. Results: The mean logMAR uncorrected distance visual acuity improved from 0.92 ± 0.60 preoperatively to 0.33 ± 0.33, 0.28 ± 0.25, 0.24 ± 0.20, and 0.27 ± 0.27 at 6, 12, 24, and 36 months postoperatively ( P < 0.001), respectively. The mean logMAR corrected distance visual acuity improved from 0.62 ± 0.65 preoperatively to 0.17 ± 0.29, 0.13 ± 0.21, 0.07 ± 0.16, and 0.11 ± 0.23 at 6, 12, 24, and 36 months postoperatively ( P < 0.001), respectively. The mean endothelial cell density decreases were 50.7% ± 21.1%, 50.8% ± 19.8%, 60.7% ± 16.6%, 62.2% ± 11.8%, and 61.8% ± 20.0% at 6, 12, 24, 36, and 48 months after surgery, respectively. Similar trends, although with slightly better visual outcomes, were found in the subgroup of patients without other eye diseases. The mean final deviation from intended spherical equivalent was 0.77 ± 1.19 D, representing a hyperopic shift. Conclusions: A combined procedure of cataract surgery, IOL implantation, and DMEK-S is an effective method of treatment in patients with combined corneal disease and cataract, maintaining visual rehabilitation in the long term. Future developments should be performed to minimize the incidence of complications. Abstract : Supplemental Digital Content is Available in the Text.